The Obama administration and the Americas : agenda for change, por : Abraham F. Lowenthal, Theodore Piccone y Laurence Whitehead (eds.), Washington : The Brookings Institution Press, 2009 - Sánchez G., Walter (Estudios Internacionales, 2009)
-